Interactions between DASH-style diet and ADIPOQ and ARL15 genes polymorphisms on blood pressure and central obesity in Iranian adults - Mehdi Mollahosseini; Zeinab Yazdanpanah; Azadeh Nadjarzadeh; Masoud Mirzaei; Seyed Mehdi Kalantar; Hamid Reza Ashrafzadeh; Khadijeh Mirzaei; Hassan Mozaffari-Khosravi (Scientific Reports)
Abstract This study aimed to investigate the interactions between the Dietary approaches to stop hypertension (DASH) and the rs1501299 and rs6450176 SNPs in terms of cardiometabolic risk factors. This cross-sectional study was conducted on 387 adults (20–70 years old) residing in Yazd, Iran. The participants were selected from participants in the recruitment phase of the Yazd Health Study (YaHS) which is a population-based cohort of 9,962 adults. The genotypes of rs1501299 and rs6450176 SNPs were determined using the restriction fragment length polymorphism (RFLP) method. Unlike for the G allele carriers of rs1501299, high adherence to the DASH dietary pattern was related to the lower diastolic blood pressure (DBP; P-interaction = 0.014) and systolic blood pressure (SBP; P-interaction = 0.051) in the participants with TT genotype. Moreover, in individuals with the AA genotype of rs6450176 SNP, adherence to this diet was associated with lower SBP (P-interaction = 0.012), waist-to-hip ratio (WHR; P-interaction = 0.026) and waist-to-height ratio (WHtR; P-interaction = 0.040), while in G allele carriers, the mean of these items was greater in individuals with high adherence to the DASH diet. The results suggest that following the DASH diet may be related to lower blood pressure and central obesity indices only in individuals with TT genotype of rs1501299 and AA genotype of rs6450176, respectively, whereas it can be associated with higher WHR and WHtR in G allele carriers of rs6450176.